BIOINTENSIVE MANAGEMENT OF SOIL-BORNE DISEASES OF FRENCH BEAN (Journal of Plant Disease Sciences, 2023)
The experiment was conducted in the experimental farm of AICRP on Vegetable, VNMKV, Parbhani during Rabi season using the local variety. The plot size (5 m x 3 m) with plant spacing 40 x 20 cm was laid out in Randomized Block Design (RBD) with four replication of each seven treatment. The rseults revealed that, significantly the lowest soil borne disease incidence ( Root rot complex) on French bean wasrecorded (7.79%) in the treatment T5 (Seed treatment by talk based Trichoderma asperellum + Bacillus subtillis (CRB-7)@ 10 g/kg seed and soil drenching @ 1 % in root zone at the time of earthing) followed by treatments T1 (Seed treatment by talk based Trichodermaasperellum (IIVR) @ 10 g/kg seed and soil drenching @ 1 % in root zone at the time of earthing)(9.89 %). Among all, the treatment T5recorded highest yield (87.1q/ha) followed by the treatment T1 (86.8 q/ha) which was statistically significant overall other treatment, whereas control recorded the lowest fruit yield (67.3q/ha). Also the maximum shoot length and root length in cm 25 DAS was found intreatment T5 with 37.02 and 27.29 cmrespectively followedby the treatment T1
Keywords: Root rot complex; Biointensive; Management,; Frenchbean